SOCIO-PRAGMATIC PROFILING ON ENGLISH IMPERATIVE INTONATION AT THE AIRPORT - Pinem, Yune Andryani (LLT Journal: A Journal on Language and Language Teaching, 2021)
Regardless its function to order someone to do or not do something, commanding and requesting is different in pragmatics and sociolinguistics basis. Related to dual-service of security and comfort at the airport, authority and politeness entailed in an imperative utterance can be expressed differently according to the context. Social backgrounds including gender, occupation and job experience or training of 6 aviation workers portray various expressions and pitches of 5 imperative operators in 10 different situations divided by level of danger. Profiling on implicature over those backgrounds are described by locating stress point switch on the expression given.